Lean implementation and productivity in Malaysian Public Emergency Departments / Tiong Ngee Wen - Tiong , Ngee Wen (2019)
Lean healthcare research has been growing since early 2000 when the quality management approach was adopted to assist with operational issues faced by healthcare institutions. Although lean healthcare has been adopted rapidly, studies have shown that limited understanding of lean healthcare may lead to an undesirable outcome and even more wastages in the institution. Through a systematic review, three gaps have been identified from the existing lean healthcare literature, namely lack of lean evaluation from the perspective of productivity, lack of comparison between high and low performance lean unit as well as a limited explanation on how lean healthcare may improve the productivity performance. Therefore, this research aims to provide an explanation of the lean implementation process that leads to the productivity level achieved by the lean healthcare adopters. This research investigated the Malaysian public emergency departments (ED), which have recently adopted lean healthcare to cope with issues on long waiting time and congestion in the department. A sequential mixed method approach was chosen to provide answers to the research questions posted. In Phase 1, a quantitative method through slack-based measure data envelopment analysis (SBM-DEA) was used to examine the efficiency of 20 ED that have implemented lean healthcare. The non-parametric analysis found mixed results in the changes in productivity level achieved by lean adopters. Subsequently, the Malmquist Productivity Index (MPI) was used to assess the productivity changes between before and after lean implementation and confirmed that only some EDs experienced improvement in efficiency while others regressed in the efficiency score. The Lean Productivity Performance Quadrant (LPPQ) was developed to provide a holistic view of the productivity performance achieved by the lean adopters. Phase 2 used a qualitative case study method with a purposive sampling of an ED from each of the LPPQ for further investigation on the implementation process leading to the productivity performance achieved. The four case studies used semi-structured interview, non-participant observation and document analysis to provide information on the performance variation between the high and low performers of lean adopters. A total of 64 participants were recruited through snowballing purposive sampling for the four case studies. Three main themes emerged from the 11 codes identified from the interview transcripts, namely planning, implementation and reflection. Elements within each of the themes were cross-examined with drivers or barriers found in existing literature to explain the productivity performance achieved. The high performing lean adopters were found to exhibit superior traits in the focus, internal communication, leadership and feedback mechanism compared to low performing lean adopters. Similarly, the higher performing lean adopters also demonstrated higher adherence to the Womack’s lean principles compared to low performing lean adopters. A total of 23 propositions were developed from the findings and eventually assisted in the development of Lean Healthcare Implementation Framework (LHIF) for Malaysia public hospital context. The findings provided some theoretical contributions and practical suggestions for future lean healthcare implementation. The directions for future research were also provided.